Variability in Pediatric Brain Death Determination Protocols in the United States. (20th July 2021) - Francoeur, Conall; Weiss, Matthew J.; MacDonald, Jennifer M.; Press, Craig; Greer, David M.; Berg, Robert A.; Topjian, Alexis A.; Morrison, Wynne; Kirschen, Matthew P.
Abstract : Objective: To determine the variability in pediatric death by neurologic criteria (DNC) protocols between US pediatric institutions and compared to the 2011 DNC guidelines. Methods: In this cross-sectional study of DNC protocols obtained from pediatric institutions in the United States via regional organ procurement organizations, protocols were evaluated across 5 domains: general DNC procedures, prerequisites, neurologic examination, apnea testing, and ancillary testing. Descriptive statistics compared protocols to each other and the 2011 guidelines. Results: A total of 130 protocols were analyzed with 118 dated after publication of the 2011 guidelines. Of those 118 protocols, identification of a mechanism of irreversible brain injury was required in 97%, while 67% required an observation period after acute brain injury before DNC evaluation. Most protocols required guideline-based prerequisites such as exclusion of hypotension (94%), hypothermia (97%), and metabolic derangements (92%). On neurologic examination, 91% required a lack of responsiveness, 93% no response to noxious stimuli, and 99% loss of brainstem reflexes. A total of 84% of protocols required the guideline-recommended 2 apnea tests. CO2 targets were consistent with guidelines in 64%. Contrary to guidelines, 15% required ancillary testing for all patients and 15% permitted ancillary studies that are not validated in pediatrics. Conclusion: Variability exists between pediatric institutional DNC protocols in all domains of DNC determination, especially with respect to apnea and ancillary testing. Better alignment of DNC protocols with national guidelines may improve the consistency and accuracy of DNC determination.